The IX Iberian Congress of Ichthyology - Correia, Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents proceedings resulting from the IX Iberian Congress of Ichthyology held in Porto, Portugal from 20th to 23rd June 2022. Published conference abstracts, presented as oral or poster communications, have been previously approved by the scientific conference committee and the original research content was double peer-reviewed. Overall, the reprint focuses on fundamental and applied ichthyological research developed mainly in the Iberian Peninsula.